Sekolah Unggulan Sebagai Upaya Membentuk Generasi Bangsa Yang Berkualitas Dan Religius - Rumina, Rumina (LPPM STAI Ihyaul Ulum Gresik, 2019)
In carrying out the development of a nation, it takes a tough and qualified and moral generation. For this reason, one way to establish a quality and moral generation requires quality education. One way that can be taken to realize these ideals is to form a superior school that is expected later with a superior school will be born of generations of people who are superior and qualified to continue the struggle and development of this beloved Indonesian Nation. How to form superior schools that are expected to be able to produce qualified and religious national generations. In carrying out a country's development process, it turns out to require a formidable generation physically, mentally and spiritually. Just being physically healthy does not guarantee success, and even spiritual mental health but physically fragile, and even that will result in less than perfect results of a development. And it turns out that with a superior school, it will be able to produce a quality generation of the nation both physically, mentally and spiritually. And to form a superior school itself, an educational institution, must implement its role and function as an educational institution optimally. Besides that the factors that influence the success of an institution in order to excel must be met as a whole. Because all aspects greatly influence the development of an educational institution. For this reason, optimizing all roles and functions in each element of the institution will strongly support the realization of a superior school which will produce quality and moral output. Factors that determine the success of superior schools are internal factors that are formed from the students themselves and the external factors which include curriculum, programs, facilities, facilities and good school teachers who are able to produce generations of creative and moral personalities.